(Sobre)vivência acadêmica e pandemia da Covid-19: percepções de estudantes da Universidade Federal de Mato Grosso do Sul/UFMS - Giovana Alle Hollender Azambuja (2022)
The psychological suffering of university students has increased in recent years, as the interest of researchers into the topic. Studies have been carried out to identify recurrent symptoms and disorders, factors that influence academic experience, adaptive possibilities, among others, always pointing to the growing need of psycological assistance in universities. However, few studies have addressed the percepction of students themselves and the meanings attributed by them to this suffering, present in their narratives. This research seeks to investigative reports of academic experiences and psychological distress of undergraduate students at the Federal University of Mato Grosso do Sul (UFMS) during the Covid-19 pandemic period. The objective is to enable an expansion in the understanding of the psychological suffering of university students from their narratives about academic experiences and psychic suffering in the pandemic period. For this, the data analysis was carried out in the light of cultural studies and social psychology theorists. This is an exploratory-descriptive qualitative research with a cross-sectional for which a questionnaire was applied through an online form to UFMS undergraduate students who at some point in their academic career expressed emotional/psychological difficulties and seek psychological care offered by the university. The research presents as results the existence of difficulties emotional/psychological at different moments of the graduation, being evident the presence of constant reports of anxiety by students, especially in the pandemic period in which the demands for productivity have increased and the ways of life and interpersonal relationships have undergone considerable changes. We hope with this study contribute to the construction of effective actions at the university that make it possible to rethink relationship in the environment university, in the sense of a culture of care.